The Use Of Bookwidgets As A Web-Based Medium To Enhance Students’ Vocabulary Knowledge - Elvina Nur Tasya; Ilyas; Arni Arsyad Sultan (CV. Edujavare Publishing, 2026)
This study aimed to investigate the effectiveness of BookWidgets as a web-based learning medium in enhancing students’ vocabulary knowledge. This research employed a quantitative approach with a pre-experimental design using a one-group pre-test and post-test. The population consisted of 191 tenth-grade students at MAN 2 Bone, and 26 students were selected as the sample through random sampling. The instrument used in this study was a vocabulary test. The data were analyzed using mean scores and percentages. The findings revealed that the students’ vocabulary knowledge improved after the implementation of BookWidgets. The mean score increased from 59.27 in the pre-test to 75.92 in the post-test, with an improvement of 16.65 points. The interactive features of BookWidgets, such as quizzes, matching exercises, and games, helped students learn vocabulary more effectively by creating an engaging and interactive learning environment. It can be concluded that BookWidgets was effective in enhancing students’ vocabulary knowledge and can be used as an alternative web-based learning medium in English language teaching.